(untitled) (Research, Society and Development, 2025)
The objective of this study was to evaluate the chemical composition and availability of phytomass in rangeland, grass land and Sabia forest at different times of the year. Forage availability samples were collected in November 2023 (dry-rainy transition), March (rainy season), June (rainy-dry transition) and September (dry season) of 2024 in three pasture areas: Sabia forest, mombaça grass pasture and rangeland with abundance of mimoso grass. The statistical design used was completely randomized design with four treatments: dry-rainy transition, rain, rain-dry transition, drought and 10 replicates. The phytomass availability data were subjected to analysis of variance and the means compared by Tukey’s test at 5% probability, using the Sisvar 5.0 Software. The chemical composition of the Sabia forest showed a higher crude protein content. Mombaça grass showed greater forage availability in the rainy, rainy-dry, and dry seasons, decreasing significantly in the dry-rainy transition season to only 2197 kg DM ha-1. Rangeland with an abundance of mimoso grass showed greater variation in phytomass availability, with the dry-rainy transition season having the lowest availability (66 kg DM ha-1). Rangeland with a predominance of mimoso grass has low phytomass availability and greater variation in forage production throughout the year. It also has low crude protein content. Pasture with mombaça grass has greater forage availability and accepts higher stocking rates than rangeland rich in mimoso grass.